Pembangunan Aplikasi m-Pembelajaran Secara Realiti Maya untuk Sains Tahun 4 - Abdul Fadil, Muhammad Shahrul Iman; Wahid, Noorhaniza (Applied Information Technology And Computer Science, 2021)
Zoo mania learning application development project using virtual reality technology plays a role and serves as an application that will help users to feel the real situation in the situation. The app will display the situation inside the animal Zoo where users can do free exploration of the area in virtual reality. This app is specially made for year 4 students and above with the title of animals in unit 3 in year 4 science textbooks to help students better understand the content to be presented in a clearer and more interesting method. The application will be developed using Unity 3D software, Microsoft Visual Studio and Blender 3D. The MMCD selection method i.e. the mobile multimedia content developer methodology is used to develop this application. This app is only available for users of android devices for starters. This project is very meaningful to help students out there to learn about animal life in a more fun way on the go. This is in line with the current COVID-19 pandemic situation, which forces students to self -study online, which prevents students from learning in person to be more effective. Therefore this application will be developed to overcome the shortcomings that occur.